Hermenêutica bíblica da pastoral da juventude: cenários e aproximações a partir de Êxodo 3,1-6 - Toledo, Joilson de Souza (2016)
This research is meant to investigate the biblical hermeneutics in this history and the works of the Ministry of Youth (PJ). Begins addressing the centrality of liberation theology to pastoral of that intelligibility. Displays PJ while youth of liberation theology, so the handling of the Bible done for her occurs within this theological framework. The juvenile condition and the People Reading Bible are the basic elements to understand the scene where the young and advisors PJ interpret the Bible. In line with other reading Popular Bible productions, this dissertation makes reference to a pericope to address nuances within the Hermeneutics of Liberation. In this way reflects on Ex 3.1 to 6 recognizing this account movements calling, displacements, incantations and strangeness that possible hermeneutical paths. The exegesis of this pericope gives attention to the verbs and images present, as well as highlights the possibilities that this provides translation space. Finally brings this hermeneutical trajectory in PJ highlighting moments, approaches and approaches, as well as the manner in which the deepening Bible has been presented in the Triennial Plans. Completes presenting research approaches possibilities present in Ex 3.1 to 6 to express the biblical hermeneutics underlying militancy and subjectivities in young people participating in the PJ.